OPTIMIZATION OF LAMPUNG BATIK PRODUCTION USING THE SIMPLEX METHOD - Aldino, Ahmad Ari; Ulfa, Marchamah (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2021)
The Production and Profit optimization application in this Batik company was built to solve their problems. This application has the ability to process raw material data, working time data, production requirements data and load data for optimization calculations. The basis for calculations carried out includes optimization calculations using the Simplex Method and the tools used are Excel Solver and Python Programming. The output of this application is that how many Batik are produced based on available resources, the total cost of expenses incurred during the production process as well as gross profit and net of sales. This application can increase company profits and the percentage level of profit depending on the price comparison of sales between one product to another